Constitutio Criminalis Theresiana-corpus delicti - Feješ, Ištvan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
The paper is divided into three major parts. In the first part the author deals with the emergence of inquisition procedure and the importance of the institute of corpus delicti for this procedure. The paper emphasizes that one of the principle reasons for the introduction of the inquisition procedure was the need to entrust the state with prosecuting criminal offenders. Commencing the procedure ex officio, by state organs enabled for systemic and efficient fight against criminality. The procedure was commenced by the court ex officio after getting hold of information that a crime was committed. By establishing corpus deliciti it was confirmed that the act had really been committed, and the process could proceed from the general phase of inquisition process to the special phase, to the phase where the inquisition was conducted against a specific person. In the second part the provisions of Constitutio Criminalis Theresiana on corpus delicti are presented. They are very detailed and often casuistic, foreseeing a number of rules and exemptions.  In these provisions, in its embryonic form, a number of important procedural institutions as inspection, expertise and like are regulated. The third part is the conclusion.
Keywords: corpus delicti; Theresiana